2015
DOI: 10.18632/oncotarget.4364
|View full text |Cite
|
Sign up to set email alerts
|

Targeting chemotherapy-induced PTX3 in tumor stroma to prevent the progression of drug-resistant cancers

Abstract: The tumor microenvironment has been suggested to participate in tumorigenesis, but the nature of the communication between cancer cells and the microenvironment, especially in response to anticancer drugs, remains obscure. We determined that activation of the CCAAT/enhancer binding protein delta (CEBPD) response to Cisplatin and 5-Fluorouracil in cancer-associated macrophages and fibroblasts contributed to the metastasis, invasion, acquired chemoresistance and stemness of cancer cells by in vitro and in vivo a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 50 publications
5
63
1
Order By: Relevance
“…1A). Our previous studies suggested that CEBPD is responsive to anticancer drugs (26,27). We further assessed whether CDDP affected CEBPD expression in UCUB cells.…”
Section: Significance Of Cebpd Immunoreactivity In Ucubmentioning
confidence: 98%
“…1A). Our previous studies suggested that CEBPD is responsive to anticancer drugs (26,27). We further assessed whether CDDP affected CEBPD expression in UCUB cells.…”
Section: Significance Of Cebpd Immunoreactivity In Ucubmentioning
confidence: 98%
“…Furthermore, as well as being a reflection of an inflammatory response, CRP has also been shown to inhibit expression of N-Cadherin and can activate human monocyte tumoricidal activity [38,39]. The pentraxin family includes CRP, and the soluble pattern recognition receptor long petraxin 3 can antagonize FGF and can inhibit FGF-dependent angiogenesis and tumor growth [40], and also can alter tumor matrix and microenvironment [41,42]. Furthermore, a new generation of IL-6 inhibitors has potential in cancer therapy, by disrupting the IL-6/CRP interactions [43-45].…”
Section: Discussionmentioning
confidence: 99%
“…Despite compelling analyses suggesting PTX3 promoter methylation in certain subtypes of cancer, we strongly believe that the role of PTX3 in regulating the tumor niche is complex and entirely context dependent. For example, Chi et al determined that PTX3 is a CCAAT/enhancer binding protein delta (CEBPD)-responsive gene and displays a pro-tumor phenotype(41), including acquired drug resistance, enhanced migration, and stem-like characteristics. Given these recent findings, we believe our results further support a pro-tumor role for PTX3 in a tissue niche with activated CAFs.…”
Section: Discussionmentioning
confidence: 99%